Effectiveness of Low Cost Material to Teach Science at Primary Level - Dr. Wajiha Kanwal; Sidra Shahid; Dr. Farkhanda Jabeen (Journal of Management Practices, Humanities and Social Sciences, 2022)
The main objective of the study was to develop the interest and conceptual knowledge about science in students. For this purpose, the ‘Low-Cost Material’ concept was taught to the students using different instructional aids. The study was quantitative in nature. Experimental research design was used to check the effectiveness of low-cost material to teach science at the primary level, which were measured through pre and post-test. An action research was conducted in a public sector high school in Rawalpindi. Students of 4th grade were selected to conduct the study. Intervention was carried for one whole week. Pre-test and post-test were taken to collect data, and the collected data was analyzed using mean and t-test. The study found a significant difference between teaching of science through use of “low-cost material” and without using it. The students, when taught science by using “low-cost material, “performed significantly high on the post-test. It was concluded that using low-cost material to teach science positively affected students’ learning. The study will act as a model and guideline for science teachers at primary level to make their teaching more effective by using “low-cost material” as AV aids during science lessons. This will contribute to better science teaching in schools with low or no resources for science teaching.